Evaluation of Performance in Female Madura Cattle in Madura Island, Indonesia - Nurgiartiningsih, Veronica Margareta Ani; Budiarto, Agus; Kusmartono, Kusmartono; Suyadi, Suyadi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
This research was conducted to evaluate the performance of female Madura cattle in three districts of Madura Island (Sampang, Pamekasan, and Sumenep), known as breeding areas for purebred Madura cattle. Vital statistics of 1,040 female Madura cattle at 24 and 30 months old in Sampang, Pamekasan, and Sumenep district were measured and analysed. Mean of Body weight, chest girth, body length, and wither height of female Madura cattle at 24 months old were 191.7±17.6 kg, 133±3.0 cm, 124.0±2.1 cm, 115.7±2.9 cm, respectively, and those at 30 months old were 209.4±23.6 kg, 138.2±4.5 cm, 125.7±2.6 cm, 116.7±3.4 cm, respectively. The body weight, chest girth, body length of female Madura cattle at 24 and 30 months old in Pamekasan district (216.6±26.5 kg, 135.2±6.1 cm, 125.4±3.9 cm, and 238.0±28.5 kg, 141.5±6.7 cm, 127.9±3.5 cm, respectively) showed the highest value compared to those in Sampang and Sumenep district. Phenotypic correlation between vital statistics and body weight at 24 and 30 months old ranged between -0.43 to 0.90. Chest girth showed the positive highest correlation with body weight of female Madura cattle at 24 months old (0.24) and at 30 month old (0.90). It indicated that chest girth could be used as estimation parameter for body weight in female Madura cattle.